Effect of different substrates and organic sources on garlic (Allium sativum) morphology in the Puñutani Community, Puno Region - Huanacuni Ajrota, Víctor Cipriano (2023)
The objective of the study was to investigate the effect of the application of different organic fertilizers on the development of plant height, bulb diameter and germinated cloves of garlic (Allium sativum). A completely randomized design (DCA) was used with a total of 4 treatments with 3 repetitions. The treatments were T0: Absolute control without substrate, T1: Agricultural land proportion 1:1 with vermicompost with sheep manure, T2: Agricultural land plus Biol at 10% in aqueous dilution, T3: Agricultural land plus 10% ash from organic waste and without addition it acted as a control. Data were analyzed with the SAS GLM procedure and treatment means were compared with Tukey's test. The results showed that the addition of Biol at 10% in aqueous dilution and Vermicompost with sheep manure to the garlic crop (Allium sativum) had the most beneficial effect on germination, diameter and height of the plant. The lowest values for the analyzed characteristics of the garlic crop (Allium sativum) were found in the control group. We conclude that the use of Biol resulted in higher yields in bulb germination, plant height and bulb diameter.